Regional integration effects of the euro: What is the empirical evidence after the first years? - Martin Hallet (Spatial implications of the European Monetary Union, 2004)
Evidence on the static integration effects of the euro in the first years is difficult to identify. Changes in price differences and trade volumes before and after 1999 hardly show up and may require more time to become visible, although there tend to be considerable differences between euro and non-euro countries, probably for a number of reasons such as distance, the overall degree of integration and the exchange rate level of the euro. Regarding the dynamic integration effects some conclusions can be drawn from the long-term integration experience of the past. Economic integration in Europe, which is further progressing with the introduction of the euro, requires structural adjustment in all regions to bring about its positive welfare effects in the long run. Programmes of public expenditure will not be successful if not accompanied by sound economic policies, in particular a balanced macroeconomic policy-mix and structural reforms to enhance the efficiency of goods, labour and capital markets.
hdl:10419/59967; http://econpapers.repec.org/RePEc:zbw:arlssd:6
Keywords: 330